The Essential Role of Data and Safety Monitoring Boards (DSMBs) in Ensuring the Ethics of Global Vaccine Trials to Address Coronavirus Disease 2019 (COVID-19O). (24th March 2021) - Eckstein, Lisa; Rid, Annette; Kamuya, Dorcas; Shah, Seema K
Abstract: Coronavirus disease 2019 (COVID-19) vaccines are being developed and implemented with unprecedented speed. Accordingly, trials considered ethical at their inception may quickly become concerning. We provide recommendations for Data and Safety Monitoring Boards (DSMBs) on monitoring the ethical acceptability of COVID-19 vaccine trials, focusing on placebo-controlled trials in low- and middle-income countries. Abstract : We provide recommendations for Data and Safety Monitoring Boards (DSMBs) on monitoring the ethical acceptability of coronavirus disease 2019 (COVID-19) vaccine trials, focusing on placebo-controlled trials in low- and middle-income countries.